2003
DOI: 10.1103/physrevlett.90.075702
|View full text |Cite
|
Sign up to set email alerts
|

Chain-Length-Dependent Relaxation Scenarios in an Oligomeric Glass-Forming System: From Merged to Well-SeparatedαandβLoss Peaks

Abstract: We have studied the relaxation dynamics of a homologous series of propylene glycol based dimethyl ethers in the supercooled regime by means of broadband dielectric spectroscopy. The system is chosen in order to minimize changes of the intermolecular interactions with varying molecular weight, M. A gradual transformation from a scenario of well-separated to one of merged alpha and beta loss peaks was observed with decreasing M. The results give strong evidence for the currently debated excess wing being due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Apart for the pendant ethyl group in place of the methyl group, POB has the same chemical structure as PPG (their structures are depicted in Figure 1). PPG has been the subject of many studies, by dielectric spectroscopy 10,14,15,57,58,59,60,61,62,63 and other techniques 64,65,66,67 .…”
mentioning
confidence: 99%
“…Apart for the pendant ethyl group in place of the methyl group, POB has the same chemical structure as PPG (their structures are depicted in Figure 1). PPG has been the subject of many studies, by dielectric spectroscopy 10,14,15,57,58,59,60,61,62,63 and other techniques 64,65,66,67 .…”
mentioning
confidence: 99%
“…The main goal of our work is the investigation of the relaxation mechanism at the basis of the EW. To extend the results of previous papers [12,23,24,30], we investigated the possibility to transform the EW into a secondary peak by changing intermolecular coupling among the investigated molecules. In our work we changed intermolecular coupling by mixing the polar TBP and Qn with 3Styr.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, dielectric spectra of the trimer of propylene glycol at high pressure showed an EW that, after aging below T g , transformed into a shoulder [25]. Dielectric measurements on a family of polyalcohols and polymers showed that the secondary relaxation peak gets close to the structural with decreasing the number of repeating units, until it merges forming an EW [12,27,28]. The application of very high pressure transform the EW of threithol and glycerol into a partially merged secondary peak [27].…”
Section: Excess Wing and Johari-goldstein Relaxation In Binary Mixturmentioning
confidence: 99%
See 2 more Smart Citations